Postcolonialism towards The Osage in Killers of The Flower Moon 2023: English - Tiara Meisyarani, Zaskia; Bunyamin Faisal; Yoga Sudarisman (Prodi Tadris Bahasa Inggris, 2025)
The Movie Killers of the Flower Moon (2023) offers a powerful lens through which to examine the Osage Nation's postcolonial experiences. This analysis explores the film's depiction of colonialism's historical impact on the Osage, focusing on identity representation and oppressive power dynamics through the lens of postcolonial theory, drawing on the works of Said and Fanon. It reveals how colonial narratives perpetuate stereotypes and economic exploitation while highlighting Osage resilience and their fight for justice and cultural recognition. This research emphasizes the need to amplify marginalized voices and address the enduring legacy of colonialism, particularly exploring the intersectionality of gender and its impact on Osage women within patriarchal and colonial systems. Through a qualitative analysis of the film's narrative and cinematic elements, this study aims to illuminate the complexities of identity, power, and representation in a postcolonial context, ultimately contributing to a greater understanding of the challenges the Osage continue to face in their pursuit of equity. By shedding light on these issues, the study contributes to a deeper appreciation of the challenges that the Osage people continue to face in their pursuit of justice and equity.